2019
DOI: 10.1177/0264619619839754
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment and some of ocular problem in nursing home residents

Abstract: We decided to conduct a study to determine the prevalence of visual impairment, blindness, refractive errors, and other visual functions in nursing homes of Iran. In this cross-sectional study, 133 elderly persons were selected from seven nursing homes using proportional-to-size random sampling. A Snellen chart was used to measure visual acuity (VA). Refraction was measured in all participants using autorefractometry and retinoscopy. A cover test was applied to assess ocular deviation. Stereopsis, color vision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous studies also found an increase in the prevalence of corneal opacity with age ( 12 , 14 , 18 20 ), which was attributed to cumulative effect of exposure to environmental factors ( 18 ) increasing degenerative conditions ( 13 ), and corneal changes and reduced transparency secondary to age-related factors ( 22 , 23 ). The prevalence of many other ocular diseases increases with age ( 12 , 17 , 18 , 21 28 ), and therefore this trend was expectable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also found an increase in the prevalence of corneal opacity with age ( 12 , 14 , 18 20 ), which was attributed to cumulative effect of exposure to environmental factors ( 18 ) increasing degenerative conditions ( 13 ), and corneal changes and reduced transparency secondary to age-related factors ( 22 , 23 ). The prevalence of many other ocular diseases increases with age ( 12 , 17 , 18 , 21 28 ), and therefore this trend was expectable.…”
Section: Discussionmentioning
confidence: 99%